2009
DOI: 10.1080/17470210802585471
|View full text |Cite
|
Sign up to set email alerts
|

Is there room for the BBC in the mental lexicon? On the recognition of acronyms

Abstract: It has been suggested that acronyms like BBC are processed like real words. This claim has been based on improved performance with acronyms in the Reicher-Wheeler task, the letter string matching task, the visual feature integration task, and the N400 component in event-related potential (ERP) studies. Unfortunately, in all these tasks performance on acronyms resembled performance on pseudowords more than performance on words. To further assess the similarity of acronyms and words, we focused on the meaning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 27 publications
7
43
1
Order By: Relevance
“…This supports the view they the activate unit lexical representations. This conclusion is in line with recent evidence showing that everyday acronyms, such as STATS, FBI, and WC, have their own entries in the mental lexicon (Brysbaert et al, 2009). Furthermore, it has been shown that words and familiar acronyms engage identical processes of semantic access as reflected by the amplitudes of the N400 (Laszlo and Federmeier, 2007a,b;Laszlo and Federmeier, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…This supports the view they the activate unit lexical representations. This conclusion is in line with recent evidence showing that everyday acronyms, such as STATS, FBI, and WC, have their own entries in the mental lexicon (Brysbaert et al, 2009). Furthermore, it has been shown that words and familiar acronyms engage identical processes of semantic access as reflected by the amplitudes of the N400 (Laszlo and Federmeier, 2007a,b;Laszlo and Federmeier, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…A small number of studies have shown that acronyms and other abbreviations are integrated alongside mainstream words in mental lexicon (Besner, Davellaar, Alcott, & Parry, 1984;Brysbaert, Speybroeck, & Vanderelst, 2009 this is the case and that acronyms fit in the same mental space as common words, it is likely that they are both processed by the same system, although the exact details of the processes underpinning acronym reading are still open to debate. The current study seeks to further contribute to this discussion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of studies suggest that access to semantic from print is similar for acronyms and mainstream words (Brysbaert et al, 2009) and that lexical decision performance is not influenced by the spelling to sound regularity of the stimuli (Hino & Lupker, 1996). Therefore, differences between acronym types were investigated only in the naming task.…”
Section: Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…Petit, Midgley, Holcomb, and Grainger (2006) have found also that priming eff ects are practically as strong for visually dissimilar lower-and uppercase versions of a given lett er (e.g., g-G) as they are with more similar combinations (e.g., c-C), and this is true even when the prime is formed from parts of the opposite-case version of the target lett er, such as midsegments (Petit & Grainger, 2002). Similarly, Brysbaert, Speybroeck, and Vanderelst (2009) found that the priming of the acronyms did not depend on the lett er case in which they were presented. Th ese results have been taken as evidence for the existence of abstract lett er representations (Dufor & Rapp, 2013) that disregard lett er shape information (Arguin & Bub, 1995).…”
Section: Discussionmentioning
confidence: 90%